O estudo do lugar a partir do uso de imagens de satélites com alunos de 4ª série do ensino fundamental - Mota, Patrícia Nascimento (2007)
This work presents a methodological proposal to study the place concept through satellite images. With this proposal, the concepts of existence place for students and teachers and the relationship of the existence place and their insert in the geographical space were tried to be emphasized. This work was developed with the fourth series students and their teachers of Pinheiro Machado Fundamental Teaching School, located in the west area of Santa Maria municipal district in Rio Grande do Sul State. Like this, it was developed a didactic proposal composed of seven stages: diagnosis and questionnaires to the students concerning about their life place; use of CBERS 2 satellite image of Santa Maria (analogical); field work in the Neighborhood with use of CBERS 2 image of Santa Maria (analogical); comparison of part of Pinheiro Machado Park neighborhood between the field work and the IKONOS II satellite image (analogical); comparison among the images CBERS 2 of Santa Maria; comparison among the images CBERS 2 of São Paulo and Rio Branco cities, located respectively in São Paulo and Acre States; Axion 3D World Atlas utilization and questionnaires applications to the students and teachers. The obtained informations proved that the existence place for the students is the house, endowed with different meanings. Because the students had difficulties in the exercises regarding this theme, the understanding of the relationship of the existence place with others (insertion in the geographical space), it is already in a certain committed way. In the life place, the students represented the elements that are part of their day by day lives according to their understanding. It was verified that the students motivated themselves while using the satellite images and this favored the understanding and the recognition of the existence place. It can be inferred in that way that the activities at the existence place developed with larger efficiency. Teachers have presented some limitation about satellite images uses; however they are interested in using these resources in the fundamental teaching, opening possibilities for a larger integration between the remote sensing and the teaching processes.